2014
DOI: 10.13068/2000-6217.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Bland vita, svarta och grå "svanar" i det reformerade svenska pensionssystemet

Abstract: Bland vita, svarta och grå "svanar" i det reformerade svenska pensionssystemet Lars Harrysson & Erika Werner sammandrag: Det reformerade allmänna svenska pensionssystemet har hyllats av många, inte minst av dem som deltagit i själva utarbetandet av systemet, men hur upp levs några av de mer grundläggande antagandena bakom reformen av dem det avser att ge ekonomiskt skydd åt på ålderdomen? Genom ett omfattande djupintervjumaterial visar Lars Harrysson och Erika Werner att det finns såväl stöd som brist på det s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Uncertainty is a well-established concept to describe contemporary views of the future (Beck, 2000; Castel, 2009). A study conducted on how much Swedish people know about pensions confirmed their feelings of insecurity in relation to their future retirement (Werner, 2012; Harrysson and Werner, 2014). However, and somewhat contrary to these earlier results, the interviewees in our study are clearly conscious of how their financial future as retirees will unfold.…”
Section: The Future – Security or Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty is a well-established concept to describe contemporary views of the future (Beck, 2000; Castel, 2009). A study conducted on how much Swedish people know about pensions confirmed their feelings of insecurity in relation to their future retirement (Werner, 2012; Harrysson and Werner, 2014). However, and somewhat contrary to these earlier results, the interviewees in our study are clearly conscious of how their financial future as retirees will unfold.…”
Section: The Future – Security or Uncertaintymentioning
confidence: 99%
“…The lifetime income is the basis for the income pension. Willingness and ability to make the right choices are central aspects, but the possibility and opportunity to make such choices varies considerably from person to person (Harrysson and Werner, 2014). The new principle applies to everyone, but still, the principle has a larger impact on the pension outcome for groups with less time in paid employment, e.g.…”
mentioning
confidence: 99%